Study of Crumb Rubber as Binder Material in Asphalt - SOI LEE CHIA; MOHD ZAMRI JAMALUDIN; ABDUL MUIZ ABD RAJAK HAMIM (Journal of Civil Engineering and Infrastructure Technology, 2023)
Asphalt is a mixture of aggregates, bitumen, quarry dust, and cement. As an addition in hot mix asphalt mixtures, recycled tire rubber known as "crumb rubber" is regarded as an environmentally friendly building practice. The laboratory hot mix asphalt design tests were conducted according to Marshall method procedure. In this study, three different crumb rubber contents (10%, 15%, and 20% by weight of bitumen), and three different bitumen contents (4%, 5%, and 6%) with a penetration grade 60/70 were investigated. The Marshall stability value and durability properties were taken into account in a comparison study between the standard and modified asphalt concrete mixtures. The strength and performance of asphalt mixtures tended to improve with the addition of crumb rubber. As some of the test results were within the acceptable range, the findings indicated that crumb rubber is advised for use as an addition in asphalt mixtures. Besides, the durability of asphalt mixtures also needed to be concerned.